Temporal analysis of dissolution by-products and genotoxic potential of spherical zinc–silicate bioglass: "Imageable beads" for transarterial embolization. (October 2014) - Hasan, MS; Kehoe, S; Boyd, D
Embolization of vascular tumors is an important tool in minimally invasive surgical intervention. Radiopaque, non-degradable, and non-deformable spherical zinc–silicate glass particles were produced in a range of 45–500 μm. Three size ranges (45–150, 150–300, and 300–500 μm) were used in the current study. The glass microspheres were eluted in polar (saline solution) and non-polar (dimethyl sulfoxide) medium, and ion release profiles were recorded using inductively coupled plasma atomic emission spectroscopy. Approximately 80% of Gaussian distribution was achieved by simple sieving. The ions released from the microspheres were dependent upon surface area to volume ratio as well as the nature of elution media. Greater ions were released from smaller particles (45–150 μm) having largest surface area in polar medium. For the genotoxicity bacterial mutation Ames assay, the concentrations of all the ions were well below their therapeutic concentration reported in the literature. No mutagenic effect was observed in the bacterial mutation Ames test. Hence, it can be concluded that the glass microspheres produced herein are non-mutagenic further supporting the materials potential as a suitable embolic agent.